2020
DOI: 10.3844/ajbbsp.2020.462.472
|View full text |Cite
|
Sign up to set email alerts
|

High-Protein Solid-State Symbiotic Fermentation of Sauce Residue for Probiotic Feed

Abstract: The abuse of antibiotics in animal feed has caused a series of problems in livestock breeding, meat products and the natural environment. In this study, sauce residue was used as the main raw material that includes 25.98% of dry-based crude protein, 3.91% of NaCl, 16.28% of crude fat, 11.06% of the ash and the multi-strain solid-state symbiotic fermentation technology was used to increase the amount of probiotics and the crude protein content of feed. Meanwhile, the addition of functional probiotics improved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The main reason was that bran, as a carbon source and a solid support, loosen the solid substrate and overcame the agglomeration of the substrate, causing better oxygen supply for the growth of mixed strains (32). Several reports had found that monosaccharide glucose was the best carbon source for yeast growth (21,35). Excessive amount of PQ caused insufficient contact between fermentation substrate and strains, while too small amount of PQ and insufficient nutrients to meet the growth needs of mixed strains.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason was that bran, as a carbon source and a solid support, loosen the solid substrate and overcame the agglomeration of the substrate, causing better oxygen supply for the growth of mixed strains (32). Several reports had found that monosaccharide glucose was the best carbon source for yeast growth (21,35). Excessive amount of PQ caused insufficient contact between fermentation substrate and strains, while too small amount of PQ and insufficient nutrients to meet the growth needs of mixed strains.…”
Section: Discussionmentioning
confidence: 99%